The effects of a highly bioavailable curcumin PhytosomeTM preparation on the retinal architecture and glial reactivity in the GFAP-IL6 mice - Pérez-Fernández, Víctor; Thananjeyan, Akshaya Lakshmi; Ullah, Faheem; Münch, Gerald; Cameron, Morven; Gyengesi, Erika (Frontiers in Ophthalmology, 2023)
Uncontrolled, chronic inflammation in the retina can disturb retinal structure and function leading to impaired visual function. For the first time, in a mouse model of chronic neuroinflammation (GFAP-IL6), we investigated the impact of chronic glial activation on the retinal microglia population and structure. In addition, we tested a curcumin PhytosomeTM preparation with enhanced bioavailability to investigate the effects of a cytokine-suppressing anti-inflammatory drug on retinal architecture. Curcumin PhytosomeTM was fed to 3-month old GFAP-IL6 mice for 4 weeks and compared to their untreated GFAP-IL6 counterparts as well as wild type mice on control diet. Microglial numbers and morphology together with neuronal numbers were characterized using immunohistochemistry and cell reconstruction in the retina, using retinal wholemount and slices. GFAP-IL6 mice showed a significant increase in Iba1-labelled mononuclear phagocytes, including microglia, and displayed altered glial morphology. This resulted in a reduction in cone density and a thinning of the retinal layers compared to wild type mice. Curcumin PhytosomeTM treatment contributed to decreased microglial density, significantly decreasing both soma and cell size compared to control diet, as well as preventing the thinning of the retinal layers. This study is the first to characterize the impact of chronic retinal inflammation in the GFAP-IL6 mouse and the therapeutic benefit of enhanced bioavailable curcumin PhytosomeTM to significantly reduce microglia density and prevent neuronal loss. These data suggest that curcumin could be used as a complementary therapy alongside traditional treatments to reduce associated retinal inflammation in a variety of retinal diseases.